Genomic epidemiology and public health implications of zoonotic monophasic Salmonella Typhimurium ST34 - Xiaolei Wu; Jiaxin Du; Xiao Zhou; Xianqi Peng; Chenghao Jia; Baikui Wang; Beibei Wu; Yan Li; Yan Li; Min Yue; Min Yue; Min Yue (Frontiers in Cellular and Infection Microbiology, 2025)
BackgroundMonophasic Salmonella Typhimurium sequence type 34 (mSTM ST34) has emerged as a significant global health threat, but our understanding of its genomic epidemiology and potential public health implications in international and regional contexts remains limited. This study aims to fill this crucial gap by assessing the genomic epidemiology of multidrug resistance (MDR) mSTM ST34, as well as its clinical characteristics and virulence.MethodsTo achieve the objectives of this study, we conducted a comprehensive genomic analysis of mSTM ST34 isolates. We obtained a global dataset comprising 13,844 strains from public databases, along with 339 strains from a regional surveillance collection in Zhejiang Province, China. This dataset aims to provide in-depth insights into antimicrobial resistance, mobile genetic elements, and pathogenicity. Additionally, we meticulously assessed the association between phenotypic profiles and clinical presentations.ResultsOur findings revealed that the prevalence of mSTM ST34 has surpassed that of the previously dominant ST19. In addition, we observed an increase in the detection of the IncQ1 plasmid, which is responsible for disseminating MDR. The prevalence of mSTM ST34 carriage was exceptionally high among children (≤12 years old) and elderly individuals (≥65 years old), with 92.6% of the isolates exhibiting MDR, including resistance to frontline antimicrobials such as third-generation cephalosporins and ciprofloxacin. Additionally, the human mSTM ST34 strain demonstrates a remarkable capacity for biofilm formation, which increases its virulence in animal models and complicates therapeutic interventions.ConclusionsmSTM ST34 has surpassed the previously dominant ST19, and its ability to transmit across multi-species increases its potential for further human transmission. This study addresses critical gaps in our understanding of mSTM ST34 prevalence, highlighting the importance of whole genome sequencing in surveilling zoonotic pathogens.